Effects of Age and Sex on Subcortical Volumes - Wang, Yanpei; Xu, Qinfang; Luo, Jie; Hu, Mingming; Zuo, Chenyi (Frontiers in Aging Neuroscience, 2019)
Purpose: In an increasingly ageing society, it is of great importance to consider trajectories of subcortical volumes at different ages for understanding biological markers of ageing. Thus, we investigated sex, age and their interactions on subcortical volumes, including the basal ganglia, thalamus, hippocampus and amygdala. Methods: We analysed the adult lifespan trajectory of subcortical volumes and asymmetries in 563 healthy subjects aged from 19 to 86 using magnetic resonance imaging (MRI) data from the publicly available IXI data set. Results: The sex made strong contributions to the trajectories of subcortical volumes with aging, including the right putamen, right pallidum, bilateral thalamus, hippocampus and amygdala. The volume of the right putamen, right pallidum and right thalamus decreased more rapidly in males than in females. The asymmetry in the hippocampus decreased only in the males and not in the females. Changes in the accumbens and pallidum fit quadratic trajectories, in which females increased until 39.26 years old in the accumbens asymmetry and then began to rapidly decline, males showed a linear decline. Conclusions: The results suggest that compared with females, males have a faster decline in the volume of the right putamen, right pallidum and right thalamus. The findings may be significant to investigate the occurrence and prevalence of degenerative brain disorders in males and females. Future study can focus on the functional and behavioural relations with subcortical structures for preventive measures of related disorders.